Targeting mTOR in HIV-Negative Classic Kaposi's Sarcoma - Merimsky, Ofer (Hindawi Publishing Corporation, 2008)
A 66-year old female with HIV-negative classic Kaposi's sarcoma responded to mTOR targeting by rapamycin. The response was well documented by PET-CT. This case provides supporting evidence that the mTOR pathway may be important in the tumorigenesis of KS and that rapamycin may have activity in this disease.